Non-equilibrium electron transport induced by terahertz radiation in the topological and trivial phases of Hg1−xCdxTe - Galeeva, Alexandra V.; Artamkin, Alexey I.; Kazakov, Alexey S.; Danilov, Sergey N.; Dvoretskiy, Sergey A.; Mikhailov, Nikolay N.; Ryabova, Ludmila I.; Khokhlov, Dmitry R. (Beilstein Journal of Nanotechnology, 2018)
Terahertz photoconductivity in heterostructures based on n-type Hg1−xCdxTe epitaxial films both in the topological phase (x < 0.16, inverted band structure, zero band gap) and the trivial state (x > 0.16, normal band structure) has been studied. We show that both the positive photoresponse in films with x < 0.16 and the negative photoconductivity in samples with x > 0.16 have no low-energy threshold. The observed non-threshold positive photoconductivity is discussed in terms of a qualitative model that takes into account a 3D potential well and 2D topological Dirac states coexisting in a smooth topological heterojunction.
Keywords: terahertz radiation; topological insulator; photoconductivity